KEBIJAKAN ANGGARAN PEMBIAYAAN PADA APBD KABUPATEN SEMARANG TAHUN ANGGARAN 2013 - Yusuo Putra Darmawan; Wiwik Widayati; Sulistyowati . (Journal of Politic and Government Studies, 2015)
The Regional Budget Revenue and Expenditure (APBD) is a concrete form of local government’s work plans that is expressed in the form of money to achieve the goals or targets in one fiscal year that are discussed and approved jointly by local government and legislative, then adjusted in the form of local regulations. One of the component in the APBD is regional financing, which encompasses all of the financial transactions of local government, including earnings and expenditures, which need to be paid or be received back. It is mainly intended by the local government budgeting to cover the deficits and surplus or to make use of. On 2013 Semarang Regency’s financing budget has increases by 600% from assignment budget to adjustment budget. The aims of this research is to find out the cause of the high nominal progression in Semarang Regency’s financing budget in 2013 fiscal year. In addition, the writer wants to explain the source and allocation of financing budget on APBD in 2013.            The method uses in this research is a qualitative method, which focuses on descriptive research. In this research the writer studied and reviewed the data in the form of numbers, doing cross-examining with Regional Development Planning Board (BAPPEDA), Department of Finance Income and Assets Management Area (DPPKAD), and stakeholders that are involved in the budget process arrangement. In this study the writer examines data from Semarang Regency’s APBD, particular in 2013, as well as other supporting data which support this research.            Through several interviews and analysis of related data, the writer discovers that the increase of Semarang Regency’s financing budget is occurred due to the increase of rest of the more budget calculation (SILPA) from assignment budget to adjustment budget, particularly in the located-SILPA. Moreover, the writer also discovers that the high level progression in financing budget are caused by financing mechanisms and the lack of time in the budget implementation, thus it causes a build up of funds in the adjustment budget.            To minimize the build up in adjustment budget, Semarang Regency Government is expected to have courage to allocate the located-SILPA, particularly on assignment-budget, so the budget implementation have a longer period, and the budget expenditures will be more effective. Keywords : The Regional Budget Revenue and Expenditure (APBD), Financing Budget, Rest of the More Budget Calculation (SILPA)